2015
DOI: 10.1055/s-0034-1393303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the histopathological effects of two electrosurgical currents in an in vivo porcine model of esophageal endoscopic mucosal resection

Abstract: In an in vivo porcine survival model of esophageal endoscopic mucosal resection, the use of MCC resulted in significantly less deep thermal ulceration, necrosis, and acute inflammation compared with LPCC. MCC should be used in preference over LPCC for esophageal endoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We considered that the actual current flowing locally could be approximated by subtracting the standby current from the working current during ESD. The study used a resected porcine esophagus, which may differ from human esophageal tissue 21 . Since there is no thermography that can be used in the esophagus of a living porcine, we conducted this experiment using the extracted esophagus of porcine.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that the actual current flowing locally could be approximated by subtracting the standby current from the working current during ESD. The study used a resected porcine esophagus, which may differ from human esophageal tissue 21 . Since there is no thermography that can be used in the esophagus of a living porcine, we conducted this experiment using the extracted esophagus of porcine.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, potassiumcompetitive acid blockers with the advantages of higher acid suppression over conventional PPIs might promote ulcer healing 21,22 Fifth, the cutting current, especially ENDO CUT mode, was reported to attenuate the inflammation and fibrosis of ulcer after esophageal ESD compared with the coagulation current. [23][24][25] Thus, the difference among electrosurgical unit modes might be a potential confounding factor. However, this factor could not be quantified, because different electrosurgical unit modes were used during the procedure, depending on the submucosal condition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This mode is designed to realize submucosal dissection with lowest tissue damage by combining cutting current and lowest peak voltage coagulation current. Bahin et al examined inflammation after endoscopic mucosal resection and showed that ENDO CUT mode resulted in less inflammation of the submucosal layer and muscle layer than COAG mode 20 . Similar to their result, in our study, lower fibrosis of the muscle layer was observed in ENDO CUT mode than in all coagulation modes.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the study is the use of a porcine model which may differ from human in certain aspects. For example, the submucosa and muscle layer are thinner in pigs than in the human esophagus 20 . Damage to the muscle layer, caused by electrocautery, may differ in the human esophagus.…”
Section: Discussionmentioning
confidence: 99%